Schooltime's contribution to pupils' physical activity levels: A longitudinal study - Johansen, Martine Amalie; Mikalsen, Hilde Kristin; Lagestad, Pål Arild (Frontiers in Public Health, 2023)
PPupils spend a significant portion of their time at school. As a result, the school serves as an important setting for both learning and the formation of healthy behaviors. Many children, and even fewer young people, do not fulfill the (inter)national health recommendations of 60 minutes of moderate to vigorous physical activity (MVPA) per day. The aim of this study was to examine pupils' MVPA during schooltime in a longitudinal perspective, including the transition from primary to secondary school. The MVPA of 234 pupils' was measured objectively using accelerometer monitors for seven consecutive days, in the spring of 2017, 2018, and 2019. Statistical analyses by Friedman, Wilcoxon and Mann-Whitney U test were used to answer the research questions. The results showed a significant decrease in the pupils' MVPA and fulfilment of health recommendations during schooltime, from 7th to 8th grade. The analyses also showed that MVPA during schooltime was higher among boys than girls, and also contributed more to boys’ fulfilment of the health recommendations at all three time periods. The results indicates that the transition between primary and secondary school is vulnerable concerning pupils' MVPA during schooltime. As schooltime accounted for significantly more MVPA for boys than for girls at all three time periods, we question whether physical activity is sufficiently facilitated for girls in school.